Measuring the Impact of Food Immunotherapy on Health-Related Quality of Life in Clinical Trials - Lloyd, Melanie; Dunn Galvin, Audrey; Tang, Mimi L. K. (Frontiers in Allergy, 2022)
Food allergy is a common, and often lifelong, disorder with considerable negative impact on the quality of life of those affected and their families. While several promising immunotherapies for food allergy have either been approved or are in late-phase clinical trials based on demonstrated effectiveness at inducing desensitization, evidence of benefit in terms of improving patient-centered outcomes is inconsistent. Historically, health-related quality of life has not been prioritized as an endpoint in food immunotherapy trials and, even when included, findings have been undermined by methodological limitations of the measurement instruments used and issues with data interpretation. This review highlights the importance of measuring health-related quality of life as an endpoint in food immunotherapy trials and discusses the strengths and limitations of available evidence in this regard, with a focus on the appropriate use of assessment instruments and interpretation of findings. There remains much to learn regarding the impact of food immunotherapies on patient wellbeing, both during treatment and over the longer term. Our aim is to assist clinicians, researchers, policy makers and consumers in their interpretation of the existing literature, and to promote greater scientific rigor in the design and selection of outcome measurement frameworks for future studies evaluating the efficacy of immunotherapy treatments for food allergy.